2013
DOI: 10.1002/adma.201204271
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Oligoelectrolytes Increase Power Generation in E. coli Microbial Fuel Cells

Abstract: A series of conjugated oligoelectrolytes with structural variations is used to stain E. coli. By taking advantage of a high-throughput screening platform that incorporates gold anodes, it is found that MFCs with COE-modified E. coli generate significantly higher power densities, relative to unmodified E. coli. These findings highlight the potential of using water-soluble molecules inspired by the work on organic semiconductors to improve electrode/microbe interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 29 publications
3
87
1
Order By: Relevance
“…21,27 In contrast to previous reports, the IM remains primarily intact under our experimental conditions. 9 Since the conditions described herein closely mimic that used in MFCs, it is unlikely that the increased extracellular electron transfer (EET) in MFCs is due to cell lysis.…”
Section: 8contrasting
confidence: 53%
See 2 more Smart Citations
“…21,27 In contrast to previous reports, the IM remains primarily intact under our experimental conditions. 9 Since the conditions described herein closely mimic that used in MFCs, it is unlikely that the increased extracellular electron transfer (EET) in MFCs is due to cell lysis.…”
Section: 8contrasting
confidence: 53%
“…45%. Given that the DSSN+ exposure in these experiments do not cause measurable cytotoxicity, 10,21,22 these data indicate DSSN+ is able to increase OM permeability without signicantly altering E. coli cell viability. These observations demonstrate that scenario (i), namely enzyme transport across the OM, is accelerated for cells that are treated with DSSN+.…”
Section: -38mentioning
confidence: 95%
See 1 more Smart Citation
“…DSSNϩ, 1,4-bis(4Љ-(N,N-bis(6ЉЉ-(N,N,N-trimethylammonium)hexyl)amino)-styryl)benzene tetraiodide (DSBNϩ), and 1,4-bis(4Љ-(N,N-bis(6ЉЉ-(N,N,N-trimethylammonium)hexyl)amino)-styryl)-2,3,5,6 tetrafluorobenzene tetraiodide (4F-DSBNϩ) were synthesized as reported previously (2,11). The MIMs used in this study were selected because their biotechnological potential had been demonstrated previously in bioelectrochemical systems and because interesting interactions with microbial cells have been documented (1,3,10).…”
Section: Methodsmentioning
confidence: 99%
“…In this contribution, we examine the response of selected Gram-negative and Gram-positive organisms to three OPV-COE MIMs that have been the focus of previous studies (1,3,9,10). Furthermore, using a combination of specific deletion mutants along with a model membrane system, we will explore interactions between OPV-COEs and different components of the cellular envelope.…”
mentioning
confidence: 99%